The Learning Loop Effect: Exploring the Role of Continuous Learning and its Implication on Agility in Large Swedish Organizations - Björling,Eleonore Karin Marie; Sohlberg,Ellen (2025)
This thesis explored how large Swedish organizations leverage continuous learning to enhance organizational agility in response to the challenges of operating in a VUCA (Volatile, Uncertain, Complex, and Ambiguous) world. The aim was to examine how learning initiatives are enhancing and sustaining organizational agility in two case companies, one in entertainment technology and one in industrial technology, with differing decentralized structures and histories. This study adopted an abductive qualitative research approach, guided by a theoretical framework synthesizing four core concepts: VUCA World, Organizational Agility, Learning Culture, and Continuous Learning. Data were collected through ten semi-structured interviews with key stakeholders across both companies and analyzed using pattern matching as a method. A coding structure based on the four aforementioned concepts was used to categorize and interpret the data. The findings revealed that both companies actively engage with challenges in the VUCA world by embedding continuous learning and agility into their strategic and operational practices. Despite the differences in sectors, company age and organizational structure, both companies emphasized the importance of decentralization, self-driven learning, and a combination of formal and informal learning initiatives to enhance organizational agility. Key findings highlighted the use of feedback loops, knowledge sharing and managerial engagement in learning as enablers of this agility. The study concluded that cultivating a learning culture is fundamental in building organizational agility, where organization-wide commitment is required. The findings contribute to the broader literature on organizational agility and learning in organizations by offering insights in how learning strategies can support adaptability in dynamic environments.
Keywords: VUCA World; Continuous Learning; Learning Culture; Organizational Agility; Decentralization